Effect of drop height on different parameters of drop jump amongsoccer players - Thapa, Rohit Kumar; Kumar, Amar; Sharma, Deepak (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Drop jump is one of the most researched plyometric exercises. Different drop heights were earlier investigated for ground reaction forces, biomechanical analysis, and other parameters. There has been no research into the influence of drop height on maximum jump height during drop jump among soccer players. Aim of Study. This study aimed to find out the optimal drop height for maximum vertical jump height in drop jumps. Material and Methods. The researchers selected 17 male soccer players (mean ± SD; age 21 ± 2 years, height 174 ± 8 cm, body mass 63 ± 5 kg, isometric leg strength 122 ± ± 18 kg) for the study. Drop jump from different heights (35 cm, 45 cm, 50 cm, 65 cm, and 72 cm) was investigated for jump height, take-off force, take-off speed, impact force, maximum concentric power, and peak speed. Results. Repeated measures ANOVA revealed significant difference in jump height from different drop height (F2.54,40.59 = 5.605, p = 0.004, partial η2 = 0.259). Post-hoc analyses through Bonferroni adjustment showed significant differences between jump height from 35 cm box and 45 cm box (t16 = 4.31, p = 0.001, d = 0.47) and 35 cm box to 72 cm box (t16 = 3.52, p = 0.003, d = 0.60). However, no significant differences could be observed in take-off force, impact force, maximum concentric power, peak speed, and take-off speed from different drop heights. Isometric leg strength were significantly correlated with jump height from 35 cm (p = 0.014), 45 cm (p = 0.021) and 50 cm (p = 0.022) drop height. Conclusions. The study concludes that to improve maximum jump ability of soccer players, box height ranging around 65 cm to 72 cm may be selected for training purposes and thus may help improve the body’s ability to convert the momentum generated by a run to maximum vertical height
Keywords: drop jump; drop height; jump height; soccer players